Genetic Polymorphism of Secretoglobin SCGB1A1 and Development of Lung Pathology in Children - N.K. Malaya; N.N. Kaladze; K.D. Maly (Zaslavsky O.Yu., 2014)
The purpose of investigation - to study of A(38)G genetic polymorphism of the first exon of secretoglobin SCGB1A1 in Crimean children and to identify the possible correlation between the degree of polymorphism and development of lung pathology (bronchial asthma and recurrent bronchitis). There were investigated DNA samples from children with bronchial asthma (75 persons), recurrent bronchitis (19 persons) and healthy children (20 persons) aged from 6 to 16 years. The genetic polymorphism was determined by polymerase chain reaction with method of allele discrimination with registration the results by electrophoresis. Frequency of allele combinations of genetic variants of studied polymorphism was different in patients with bronchial asthma, recurrent bronchitis and in control group. Thus, among patients with bronchial asthma the frequency of homozygous allele AA carriers is lower, and among patients with recurrent bronchitis it is higher then in control group. Contrary, the frequency of AG heterozygotes was higher among patients with bronchial asthma then in patients with recurrent bronchitis and in control group. Also the frequency of AG heterozygotes in patients with recurrent bronchitis is much lower than homozygotes. The obtained results can be used for prognostic purpose to evaluate the prospects of the obstructive syndrome development.